2022
DOI: 10.21873/cgp.20361
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Sequencing Identifies a Six-MicroRNA Signature Enabling Classification of Brain Metastases According to their Origin

Abstract: Background/Aim: Brain metastases (BMs) are the most frequent intracranial tumors in adults and one of the greatest challenges for modern oncology. Most are derived from lung, breast, renal cell, and colorectal carcinomas and melanomas. Up to 14% of patients are diagnosed with BMs of unknown primary, which are commonly characterized by an early and aggressive metastatic spread. It is important to discover novel biomarkers for early identification of BM origin, allowing better management of patients with this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The lowest sensitivity was observed in BML, which corresponds with high heterogeneity of histological types (23). These ndings and identi ed miRNA pro les are consistent with the results of Roskova et al (10). However, biopsy and subsequent histopathological examination is not always indicated due to the fragility of cancer patients and the high invasiveness of the surgical procedure or the BM localization.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The lowest sensitivity was observed in BML, which corresponds with high heterogeneity of histological types (23). These ndings and identi ed miRNA pro les are consistent with the results of Roskova et al (10). However, biopsy and subsequent histopathological examination is not always indicated due to the fragility of cancer patients and the high invasiveness of the surgical procedure or the BM localization.…”
Section: Discussionsupporting
confidence: 88%
“…The RNA input was 100 ng for tissue and 5 µl for plasma and CSF. The preparation and cDNA libraries quantity and quality control were described in detail earlier (10). Subsequently, libraries were normalized and pooled in equimolar ratio using online weight to molar quantity converter.…”
Section: Library Preparation Pooling and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identifies miR-202–3p as a critical regulator of brain metastasis and highlights the miR-202–3p/MMP-1 axis as a potential prognostic and therapeutic target. Roskova et al analyzed miRNA expression in 71 fresh frozen histopathologically confirmed BM tissues originating from five common cancer types (lung, breast, renal cell carcinoma, colorectal carcinoma, and melanoma) [ 46 ]. MiRNA sequencing and subsequent validation by RT-qPCR were used to identify 373 miRNAs with significantly different expression across the five BM groups.…”
Section: Mirnas As Therapeuticsmentioning
confidence: 99%
“…Roskova et al studied microRNAs expression in brain metastases arising from different origins, and they found that there is a significantly different expression of six microRNAs in five groups of brain metastases, including brain metastases with origin in melanomas, renal cell carcinomas, breast carcinomas, lung carcinomas, colorectal carcinomas [ 38 ]. These microRNAs include microRNA-141-3p, microRNA-141-5p, microRNA-146a-5p, microRNA-194-5p, microRNA-200b-3p, microRNA-365b-5p [ 38 ].…”
Section: Reviewmentioning
confidence: 99%